Polycaprolactone stent filled with drug-loaded polydopamine hydrogel as well as preparation method and application of polycaprolactone stent
By creating micropore structures in polycaprolactone scaffolds and filling drug-loaded polydopamine hydrogels, combined with mesoporous ceramic embedded antibacterial drugs, the shortcomings of existing scaffolds in drug release, cell adhesion and antibacterial properties were solved, and better bone tissue regeneration effects were achieved.
Patent Information
- Application Number
- CN202411966828.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing polycaprolactone stents have shortcomings in drug release, cell adhesion, mechanical strength and antibacterial properties, and it is difficult to effectively promote bone tissue regeneration.
Using a drug-loaded polydopamine hydrogel-filled polycaprolactone scaffold, a microporous structure is created between and on the surface of polycaprolactone fibers, the hydrogel is filled and the drug-loaded polydopamine is embedded, while the antibacterial drugs are embedded in the mesoporous ceramics to delay drug release.
It significantly improves the drug release performance, cell adhesion and mechanical strength of the stent, extends the antibacterial effect, enhances the induction ability of stem cell osteogenesis and differentiation, and is suitable for the regeneration and repair of bone defects.
Smart Images

Figure CN119770730A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical stents, and particularly relates to a polycaprolactone stent filled with drug-loaded polydopamine hydrogel, and a preparation method and application thereof. Background Art
[0002] An ideal bone tissue engineering scaffold should have an interconnected porous network structure, providing interconnected channels for cell migration, ion transport, and cell-to-cell interaction. Conventional techniques include foaming, sacrificial templates, freeze-drying, and casting, etc. 3D printing, also known as additive manufacturing technology, has penetrated into all walks of life due to its significant advantages in high precision, personalized manufacturing, and complex shape construction. 3D printing obtains a three-dimensional entity by stacking raw materials layer by layer on a plane. Compared with other scaffold preparation technologies, 3D printing technology can freely design the porosity and shape of the scaffold, which can well meet the needs of bone tissue engineering.
[0003] Polycaprolactone (PCL) is a commonly used material for 3D printing. It is widely used in the field of medical science because of its good biocompatibility, non-toxicity, degradability, and ability to induce tissue regeneration and provide a place for cell adhesion, proliferation and differentiation. However, the hydrophobicity of PCL affects the adhesion of the scaffold, and its mechanical structure is significantly damaged after degradation.
[0004] At present, there are many studies on polycaprolactone-based scaffolds, but the polycaprolactone-based scaffolds, polydopamine-containing drug-loaded particles, and drug-loaded ZIF8 obtained generally have the following problems: 1) Polydopamine degrades slowly, making it difficult to effectively release enough drugs to achieve antibacterial and bone-promoting effects; 2) The surface of the polycaprolactone scaffold is too hydrophobic, which is not conducive to cell adhesion and proliferation; 3) The components of the material are relatively single, making it difficult to achieve good antibacterial and bone regeneration effects; 4) The preparation process is complicated and difficult to industrialize.
[0005] Therefore, it is of great significance to provide a polycaprolactone scaffold with good osteogenic activity, drug release performance, cell adhesion and mechanical strength. Summary of the invention
[0006] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides a polycaprolactone scaffold having good osteogenic activity, drug release performance, cell adhesion and mechanical strength.
[0007] The inventive concept of the present invention is as follows: the polycaprolactone stent of the present invention comprises a polycaprolactone stent body, and a drug-loaded mesoporous ceramic and a zeolite imidazolate skeleton material embedded in the polycaprolactone stent body; the drug-loaded mesoporous ceramic is embedded in the zeolite imidazolate skeleton material; the matrix material of the polycaprolactone stent body is polycaprolactone, and the fibers between the polycaprolactone and the fiber surface of the polycaprolactone both have a micron pore structure, and the size of the micron pore structure between the fibers of the polycaprolactone is larger than the size of the micron pore structure on the fiber surface of the polycaprolactone; the micron pore structure is filled with hydrogel; and the drug-loaded polydopamine is embedded in the hydrogel. The polycaprolactone stent body of the present invention has macroscopic large pores (fiber gaps) and microscopic small pores (holes on the fiber surface), which can significantly increase the specific surface area of the polycaprolactone stent body, accelerate the degradation of polycaprolactone and release more acidic degradation products, thereby accelerating the degradation of polydopamine and accelerating the release of the antibacterial drugs embedded inside. At the same time, macroscopic macropores and microscopic small pores can also improve the surface roughness of the polycaprolactone stent body, thereby improving the cell adhesion of the polycaprolactone stent. The drug-loaded mesoporous ceramics embedded in the zeolite imidazolate skeleton material can delay the release of the drug, achieve the effect of long-term sustained and controlled release, improve the antibacterial properties, significantly induce the osteogenic differentiation of stem cells, and the mesoporous ceramics can enhance the biological activity and mechanical strength of the drug-loaded particles. In addition, the hydrogel and drug-loaded polydopamine filled in the pores of the stent can improve the mechanical strength and biological activity of the stent, give the stent antibacterial properties, and have drug sustained and controlled release properties, which can achieve better therapeutic effects through sustained and controlled release of drugs.
[0008] Therefore, the first aspect of the present invention provides a polycaprolactone stent filled with drug-loaded polydopamine hydrogel.
[0009] Specifically, the drug-loaded polydopamine hydrogel-filled polycaprolactone stent comprises a polycaprolactone stent body, and drug-loaded mesoporous ceramics and zeolite imidazolate framework materials embedded in the polycaprolactone stent body;
[0010] The drug-loaded mesoporous ceramic is embedded in the zeolite imidazolate framework material;
[0011] The matrix material of the polycaprolactone stent body is polycaprolactone fiber, and the fibers of the polycaprolactone and the surfaces of the polycaprolactone fibers have micron pore structures, and the size of the micron pore structures between the polycaprolactone fibers is larger than the size of the micron pore structures on the surfaces of the polycaprolactone fibers;
[0012] The micron pore structure is filled with hydrogel; and drug-loaded polydopamine is embedded in the hydrogel.
[0013] Preferably, the polycaprolactone stent body is a 3D printed stent.
[0014] Preferably, the molecular weight of the polycaprolactone is 27,000-110,000 Daltons; further preferably, the molecular weight of the polycaprolactone is 30,000-100,000 Daltons.
[0015] Preferably, the size of the micron pore structure between the fibers of polycaprolactone is 200-650 μm; further preferably, the size of the micron pore structure between the fibers of polycaprolactone is 200-600 μm.
[0016] Preferably, the size of the micron pore structure on the surface of the polycaprolactone fiber is 0.9-110 μm; further preferably, the size of the micron pore structure on the surface of the polycaprolactone fiber is 1-100 μm.
[0017] Preferably, the mesoporous ceramic in the drug-loaded mesoporous ceramic includes at least one of mesoporous silicon, mesoporous calcium silicate, mesoporous magnesium silicate, mesoporous zinc silicate, mesoporous strontium silicate, mesoporous bioglass, and mesoporous hydroxyapatite.
[0018] Preferably, the particle size of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 45-1100 nm; further preferably, the particle size of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 50-1000 nm.
[0019] Preferably, the specific surface area of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 140-2000m 2 / g; Further preferably, the specific surface area of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 150-1800m 2 / g.
[0020] Preferably, the average pore size of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 2-45 nm; further preferably, the average pore size of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 2-40 nm.
[0021] Preferably, the drug in the drug-loaded mesoporous ceramic includes a drug that promotes tissue regeneration and repair.
[0022] Further preferably, the drug for promoting tissue regeneration and repair includes at least one of bone morphogenetic protein-2, bone morphogenetic protein-7, vascular endothelial cell factor, platelet-derived factor, epidermal growth factor, fibroblast growth factor, keratinocyte growth factor, nerve growth factor, transforming growth factor, insulin-like growth factor, parathyroid hormone, growth hormone, interleukin, curcumin, melatonin, alendronate sodium, zoledronic acid sodium, ibandronate sodium, naringin, resveratrol, dexamethasone, gentamicin sulfate, berberine hydrochloride, gentamicin, salmon calcitonin, strontium ranelate, and vitamin D.
[0023] Preferably, the hydrogel comprises at least one of methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chondroitin sulfate, methacrylated chitosan, methacrylated carboxymethyl chitosan, methacrylated gelatin, methacrylated sodium alginate, hyaluronic acid, silk fibroin, chondroitin sulfate, chitosan, carboxymethyl chitosan, gelatin, and sodium alginate.
[0024] Preferably, the drug in the drug-loaded polydopamine includes an antibacterial drug.
[0025] Further preferably, the antibacterial drugs include at least one of ertapenem, imipenem, meropenem, piperacillin / tazobactam, amikacin, colistin, polymyxin B, amikacin, linezolid, vancomycin, tetracycline, tigecycline, fluorouracil, amphotericin B, caspofungin, voriconazole, triclosan, chlorhexidine, penicillin, roxithromycin, clarithromycin, azithromycin, tobramycin, etimicin, gentamicin, netilmicin, tetracycline, chloramphenicol, ciprofloxacin, levofloxacin, moxifloxacin, metronidazole, ornidazole, tinidazole, itraconazole, mycobacterium, and griseofulvin.
[0026] The second aspect of the present invention provides a method for preparing the polycaprolactone scaffold filled with the drug-loaded polydopamine hydrogel according to the first aspect of the present invention.
[0027] Specifically, the method for preparing the polycaprolactone stent filled with drug-loaded polydopamine hydrogel comprises the following steps:
[0028] (1) mixing a mesoporous ceramic and an aqueous solution containing a drug to obtain a drug-loaded mesoporous ceramic; mixing the drug-loaded mesoporous ceramic and an aqueous solution of 2-methylimidazole, and then adding an aqueous solution of a zinc source to react to obtain a material in which a zeolite imidazole ester framework material is embedded in the drug-loaded mesoporous ceramic;
[0029] (2) mixing polycaprolactone, a solvent, gluconolactone and the material obtained in step (1) for embedding the drug-loaded mesoporous ceramic with the zeolite imidazolate skeleton material to obtain a mixed solution, preparing the mixed solution into a film, and then printing to obtain gluconolactone / drug-loaded mesoporous ceramic@zeolite imidazolate skeleton material / polycaprolactone scaffold, and placing it in an aqueous solution, ultrasonically treating it, and obtaining drug-loaded mesoporous ceramic@zeolite imidazolate skeleton material / polycaprolactone scaffold;
[0030] (3) adding the drug-loaded polydopamine to a hydrogel solution containing a photoinitiator to obtain a hydrogel solution containing the drug-loaded polydopamine; then placing the drug-loaded mesoporous ceramic @ zeolite imidazole ester framework material / polycaprolactone scaffold obtained in step (2) into the hydrogel solution containing the drug-loaded polydopamine, then taking it out and solidifying it to obtain the polycaprolactone scaffold filled with the drug-loaded polydopamine hydrogel.
[0031] Preferably, in step (1), the mass ratio of the drug to the mesoporous ceramic is (0.0005-0.055):1; further preferably, the mass ratio of the drug to the mesoporous ceramic is (0.0005-0.05):1.
[0032] Preferably, in step (1), the mesoporous ceramic and the drug-containing aqueous solution are mixed by stirring, the stirring speed is 270-900 rpm, the stirring time is 3.5-20 h; the stirring temperature is 0-37°C; further preferably, the stirring speed is 300-800 rpm, the stirring time is 4-18 h; the stirring temperature is 0-37°C.
[0033] Preferably, in step (1), the mesoporous ceramic and the aqueous solution containing the drug are mixed and then dried to obtain the drug-loaded mesoporous ceramic.
[0034] Preferably, in step (1), the concentrations of 2-methylimidazole and drug-loaded mesoporous ceramics in the 2-methylimidazole aqueous solution are 17-58 mg / mL and 7-20 mg / mL, respectively; further preferably, the concentrations of 2-methylimidazole and drug-loaded mesoporous ceramics in the 2-methylimidazole aqueous solution are 19-53 mg / mL and 8-18 mg / mL, respectively.
[0035] Preferably, in step (1), the zinc source aqueous solution comprises an aqueous zinc nitrate solution; the concentration of zinc nitrate in the aqueous zinc nitrate solution is 5.5-33 mg / mL; further preferably, in step (1), the concentration of zinc nitrate in the aqueous zinc nitrate solution is 6-30 mg / mL.
[0036] Preferably, in step (1), the volume ratio of the 2-methylimidazole aqueous solution to the zinc source aqueous solution is (5.5-13):1; further preferably, in step (1), the volume ratio of the 2-methylimidazole aqueous solution to the zinc source aqueous solution is (6-12):1.
[0037] Preferably, in step (1), the reaction further includes a washing and drying process.
[0038] Preferably, in step (2), the mass ratio of the material of the gluconolactone and zeolite imidazolate skeleton material encapsulating the drug-loaded mesoporous ceramic to polycaprolactone is (0.45-3.3):(0.05-0.33):1; further preferably, in step (2), the mass ratio of the material of the gluconolactone and zeolite imidazolate skeleton material encapsulating the drug-loaded mesoporous ceramic to polycaprolactone is (0.5-3):(0.05-0.3):1.
[0039] Preferably, in step (2), the mass volume ratio of the polycaprolactone to the solvent is (0.45-9) g:10 mL; further preferably, in step (2), the mass volume ratio of the polycaprolactone to the solvent is (0.5-8) g:10 mL.
[0040] Preferably, in step (2), the solvent comprises dichloromethane.
[0041] Preferably, in step (2), the mixing is carried out by stirring, the stirring speed is 270-900 rpm, and the stirring time is 22-80 h; further preferably, the stirring speed is 300-800 rpm, and the stirring time is 24-72 h.
[0042] Preferably, the stirring includes any one of mechanical stirring and magnetic stirring.
[0043] Specifically, in step (2), the mixed solution is gluconolactone / drug-loaded mesoporous ceramic@zeolite imidazolate framework material / polycaprolactone solution.
[0044] Preferably, in step (2), the process of preparing the mixed liquid into a thin film is to place the mixed liquid on a flat surface and let it stand to obtain the film.
[0045] Preferably, the standing is placing in a ventilated place for 44-80 hours; further preferably, the standing time is 48-72 hours.
[0046] Specifically, in step (2), the film is gluconolactone / drug-loaded mesoporous ceramic@zeolite imidazolate skeleton material / polycaprolactone film.
[0047] Preferably, in step (2), the printing is 3D printing.
[0048] Preferably, in step (2), the printing process is to first place the gluconolactone / drug-loaded mesoporous ceramic @zeolite imidazolate framework material / polycaprolactone film into a printing barrel, match the needle, set the printing parameters and heating temperature, and then print layer by layer to obtain the gluconolactone / drug-loaded mesoporous ceramic @zeolite imidazolate framework material / polycaprolactone scaffold.
[0049] Preferably, the needle diameter is 0.18-0.45 mm; further preferably, the needle diameter is 0.2-0.5 mm.
[0050] Preferably, the temperature of the barrel is 55-95°C; more preferably, the temperature of the barrel is 60-90°C.
[0051] Preferably, the temperature of the needle is 60-95°C; further preferably, the temperature of the needle is 65-95°C.
[0052] Preferably, the fiber spacing of the polycaprolactone fibers in the polycaprolactone stent body is (0.70-0.90) mm×(0.70-0.90) mm; further preferably, the fiber spacing of the polycaprolactone fibers in the polycaprolactone stent body is (0.75-0.85) mm×(0.75-0.85) mm; further preferably, the fiber spacing of the polycaprolactone fibers in the polycaprolactone stent body is 0.8 mm×0.8 mm.
[0053] Preferably, the fiber orientation of the polycaprolactone fibers in the polycaprolactone stent body is 0-90°.
[0054] Preferably, the printing speed is 7-16.5 mm / s; further preferably, the printing speed is 8-15 mm / s.
[0055] Preferably, the air pressure during printing is 300-460 kPa; further preferably, the air pressure during printing is 320-420 kPa.
[0056] Preferably, the support layer height during printing is 70-95% of the needle diameter; further preferably, the support layer height during printing is 75-90% of the needle diameter.
[0057] Preferably, in step (2), the mass volume ratio of gluconolactone / drug-loaded mesoporous ceramic@zeolite imidazolate framework material / polycaprolactone scaffold and the aqueous solution is 1 mg:(0.27-4.5) mL; further preferably, the mass volume ratio of gluconolactone / drug-loaded mesoporous ceramic@zeolite imidazolate framework material / polycaprolactone scaffold and the aqueous solution is 1 mg:(0.3-4) mL.
[0058] Preferably, in step (2), the ultrasonic treatment time is 0.35-1.1 h; further preferably, the ultrasonic treatment time is 0.4-1 h.
[0059] Preferably, in step (2), the temperature of the ultrasonic treatment is room temperature.
[0060] Specifically, the drug-loaded mesoporous ceramic @ zeolite imidazolate skeleton material / polycaprolactone scaffold obtained in step (2) is a drug-loaded mesoporous ceramic @ zeolite imidazolate skeleton material / polycaprolactone scaffold with a multi-level pore structure, that is, the fibers between polycaprolactone and the fiber surface of polycaprolactone have a micron pore structure.
[0061] Preferably, in step (3), the preparation process of the drug-loaded polydopamine is to mix the drug and the dopamine aqueous solution, stir, and obtain; the concentration of dopamine in the dopamine aqueous solution is 1.5-4.5 mg / mL; the mass volume ratio of the drug to the dopamine aqueous solution is (9-33) mg:10 mL; further preferably, the concentration of dopamine in the dopamine aqueous solution is 1.6-4 mg / mL; the mass volume ratio of the drug to the dopamine aqueous solution is (10-30) mg:10 mL.
[0062] Preferably, the stirring speed is 270-900 rpm, and the stirring time is 3.5-13 h; further preferably, the stirring speed is 300-800 rpm, and the stirring time is 4-12 h.
[0063] Preferably, the pH value of the dopamine aqueous solution is 7.5-10; further preferably, the pH value of the dopamine aqueous solution is 8.2-9.2.
[0064] Preferably, in step (3), the concentration of the hydrogel in the hydrogel solution is 1.4-3.3%; further preferably, in step (3), the concentration of the hydrogel in the hydrogel solution is 1.5-3%.
[0065] Preferably, in step (3), the hydrogel is dissolved in a PBS solution containing a photoinitiator to obtain a hydrogel solution.
[0066] Preferably, in step (3), the mass volume ratio of the drug-loaded polydopamine to the hydrogel solution is (11-52) mg:1 mL; further preferably, in step (3), the mass volume ratio of the drug-loaded polydopamine to the hydrogel solution is (12-48) mg:1 mL.
[0067] Preferably, in step (3), the photoinitiator comprises phenyl-2,4,6-trimethylbenzoyl lithium phosphite.
[0068] Preferably, the concentration of the photoinitiator in the PBS solution is 0.22-0.45%; further preferably, the concentration of the photoinitiator in the PBS solution is 0.25-0.4%.
[0069] Preferably, in step (3), the mass volume ratio of the drug-loaded mesoporous ceramic @ zeolite imidazolate framework material / polycaprolactone scaffold to the hydrogel solution containing drug-loaded polydopamine is (0.04-0.18) g: 10 mL; further preferably, the mass volume ratio of the drug-loaded mesoporous ceramic @ zeolite imidazolate framework material / polycaprolactone scaffold to the hydrogel solution containing drug-loaded polydopamine is (0.04-0.16) g: 10 mL.
[0070] Preferably, in step (3), the insertion time is 2.5-13 min; further preferably, the insertion time is 3-12 min.
[0071] Preferably, in step (3), the curing time is 27-130 s; further preferably, the curing time is 30-120 s.
[0072] Preferably, in step (3), the solidification further includes a freezing and freeze-drying process.
[0073] The third aspect of the present invention provides a use of the polycaprolactone scaffold filled with the drug-loaded polydopamine hydrogel according to the first aspect of the present invention in the preparation of bone tissue defect repair and regeneration products.
[0074] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0075] (1) The present invention can delay the release of drugs that promote tissue regeneration and repair by encapsulating drug-loaded mesoporous bioceramics in zeolite imidazolate framework materials (ZIF8), achieving the effect of long-term sustained release, giving the multi-level porous structure polycaprolactone scaffold good antibacterial properties, and can significantly induce osteogenic differentiation of stem cells, making it more suitable for regeneration and repair of bone defects. In addition, the pore structure in the polycaprolactone fiber of the present invention reduces the mechanical strength of the polycaprolactone scaffold, and the bioactive ceramics in the drug-loaded mesoporous ceramic @ZIF8 particles filled in the fiber can enhance the biological activity and mechanical strength of the drug-loaded mesoporous ceramic @ZIF8, thereby maintaining the biological activity and mechanical strength of the polycaprolactone scaffold, making it suitable for bone repair.
[0076] (2) In the case of bone infection, the pH in the local microenvironment is low, which will significantly accelerate the degradation of ZIF8 and accelerate the release of the tissue regeneration and repair drugs loaded therein, synergistically achieving better antibacterial and bone regeneration effects. In addition, the present invention can accelerate the degradation of polycaprolactone and accelerate the release of drugs in the case of auxiliary ultrasound, thereby achieving better antibacterial and bone regeneration effects.
[0077] (3) Polydopamine degrades very slowly in vivo and in vitro. The present invention performs pore-forming treatment on the polycaprolactone fibers of the printed scaffold so that the printed scaffold simultaneously obtains macroscopic large pores (fiber gaps) and microscopic small pores (holes on the fiber surface), significantly increasing the specific surface area of the scaffold, accelerating the degradation of polycaprolactone and releasing more acidic degradation products, thereby accelerating the degradation of polydopamine and accelerating the release of antibacterial drugs embedded therein.
[0078] (4) The surface of polycaprolactone is too hydrophobic and not suitable for cell adhesion. The present invention performs pore-forming treatment on the polycaprolactone fibers of the printed scaffold so that the printed scaffold has both macroscopic large pores (fiber gaps) and microscopic small pores (holes on the fiber surface), which significantly improves the surface roughness of the scaffold and improves the cell adhesion effect of the scaffold.
[0079] (5) The present invention simultaneously fills the pores of the 3D printed scaffold with hydrogel and drug-loaded polydopamine particles. Compared with filling only with hydrogel, it can not only significantly increase the mechanical strength, but also give the scaffold antibacterial properties and enhance the biological activity of the scaffold. At the same time, filling the pores with hydrogel with good hydrophilicity can further regulate the hydrophilicity and hydrophobicity of the material while maintaining the mechanical strength of the material, making it more suitable for the regeneration and repair of bone defects.
[0080] (6) The present invention partially uses neutrally soluble methacrylated hydrogel to fill the printed scaffold, which can avoid the problem that the acidic microenvironment of the scaffold is not conducive to cell survival. In addition, when the hydrogel is sodium alginate or sodium methacrylated alginate, the divalent metal ions such as calcium ions and zinc ions released by the degradation of bioactive ceramics and ZIF8 can cross-link sodium alginate or sodium methacrylated alginate, playing a role in maintaining the mechanical strength of the hydrogel.
[0081] (7) The polydopamine of the present invention is loaded with drugs through encapsulation to form drug-loaded particles, which are then dispersed inside the hydrogel and dispersed in the pores of the stent, which makes the polycaprolactone stent have a better sustained-release drug effect. Conventionally, the adhesive effect of the polydopamine coating is used to adsorb and load drugs.
[0082] (8) The preparation method of the present invention has a simple process, low requirements on equipment, and the raw materials are readily available from industrial sources, low cost, and easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 The release curves of the drug for promoting tissue regeneration and repair in vitro from the polycaprolactone stents of Examples 1-4 and Comparative Examples 1-4, 6-7, and 10 of the present invention;
[0084] Figure 2 The release curves of the drug for promoting tissue regeneration and repair in vitro from the polycaprolactone stents of Example 1 and Comparative Examples 1-4, 6-7, and 10 of the present invention;
[0085] Figure 3 The in vitro antibacterial drug release curves of the polycaprolactone stents of Examples 1-4 and Comparative Examples 1-2, 5-8, and 10 of the present invention are shown;
[0086] Figure 4 This is an in vitro antibacterial drug release curve of the polycaprolactone stent of Example 1 and Comparative Examples 1-2, 5-8, and 10 of the present invention;
[0087] Figure 5 The alkaline phosphatase activity diagram of the polycaprolactone scaffolds of Examples 1-4 and Comparative Examples 1-10 of the present invention. DETAILED DESCRIPTION
[0088] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be noted that the following embodiments do not limit the protection scope of the present invention.
[0089] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0090] Example 1
[0091] A method for preparing a polycaprolactone stent filled with a drug-loaded polydopamine hydrogel comprises the following steps:
[0092] (1) At 0°C, 100 mg of mesoporous calcium silicate (average particle size between 300-1000 nm, specific surface area between 300 and 900 m 2 / g, with an average pore size of 2-30nm) was dispersed in 10mL of an aqueous solution containing 0.05mg of bone morphogenetic protein-2, stirred at 300rpm for 18h, and freeze-dried to obtain drug-loaded mesoporous ceramics; 300mg of the drug-loaded mesoporous ceramics was added to 24mL of a 35mg / mL 2-methylimidazole aqueous solution, and 3mL of a 14mg / mL zinc nitrate aqueous solution was added dropwise during stirring, and after the reaction, the solution was washed and freeze-dried to obtain drug-loaded mesoporous ceramics@ZIF8 particles;
[0093] (2) Dissolve 10 g of polycaprolactone (molecular weight 40,000 Daltons) in 50 mL of dichloromethane, add 10 g of gluconolactone and 1.5 g of the drug-loaded mesoporous ceramic @ZIF8 particles obtained in step (1), and stir magnetically at a speed of 500 rpm for 72 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone solution; pour the solution on a glass culture dish and place it in a ventilated state for 72 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone film; place the film in a printing barrel with a needle diameter of 0.25 m m, barrel temperature 70℃, needle temperature 75℃, fiber spacing 0.8mm×0.8mm, printing rate 10mm / s, fiber orientation "0-90°", air pressure 360kPa, scaffold layer height 80% of the needle diameter, printing layer by layer to obtain gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold; 50mg of gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was immersed in 50mL aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold;
[0094] (3) Dissolve 20 mg of gentamicin in 10 mL of 2 mg / mL dopamine aqueous solution (pH = 8.4), stir at 300 rpm for 12 min, and freeze-dry to obtain drug-loaded polydopamine; dissolve 180 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.3% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 240 mg of drug-loaded polydopamine to obtain a hydrogel solution containing drug-loaded polydopamine; place 100 mg of the multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold obtained in step (2) into the hydrogel solution containing drug-loaded polydopamine, disperse for 6 min, take out, irradiate with blue light for 90 s to solidify, then freeze in a -20°C refrigerator, and freeze-dry in a freeze dryer to obtain a drug-loaded polydopamine hydrogel filled with a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold.
[0095] Example 2
[0096] A method for preparing a polycaprolactone stent filled with a drug-loaded polydopamine hydrogel comprises the following steps:
[0097] (1) At 15°C, 100 mg of mesoporous hydroxyapatite (average particle size between 100-600 nm, specific surface area between 150-500 m 2 / g, with an average pore size of 3-40nm) was dispersed in 10mL of an aqueous solution containing 30mg of dexamethasone, stirred at 500rpm for 16h, and freeze-dried to obtain drug-loaded mesoporous ceramics; 280mg of drug-loaded mesoporous ceramics was added to 24mL of a 27mg / mL 2-methylimidazole aqueous solution, and 3mL of a 10mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the mixture was washed and freeze-dried to obtain drug-loaded mesoporous ceramics@ZIF8 particles;
[0098] (2) Dissolve 10 g of polycaprolactone (molecular weight: 100,000 Daltons) in 200 mL of dichloromethane, add 30 g of gluconolactone and 3 g of the drug-loaded mesoporous ceramic @ZIF8 particles obtained in step (1), and stir magnetically at 800 rpm for 60 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone solution; pour the solution onto a glass culture dish and place it in a ventilated state for 48 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone film; place the film into a printing barrel with a needle diameter of 0.5 mm, barrel temperature 90℃, needle temperature 95℃, fiber spacing 0.8mm×0.8mm, printing rate 8mm / s, fiber orientation "0-90°", air pressure 320kPa, scaffold layer height 90% of the needle diameter, layer by layer printing gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold; 50mg of gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was immersed in 200mL aqueous solution, ultrasonicated at room temperature for 0.8h, and a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was obtained;
[0099] (3) 30 mg of vancomycin was dissolved in 10 mL of a 4 mg / mL dopamine aqueous solution (pH = 8.2), stirred at 800 rpm for 4 min, and freeze-dried to obtain drug-loaded polydopamine; 150 mg of methacryloylated silk protein was dissolved in 10 mL of a PBS solution containing 0.35% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and 480 mg of drug-loaded polydopamine was added to obtain a hydrogel solution containing drug-loaded polydopamine; 160 mg of the multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold obtained in step (2) was placed in the hydrogel solution containing drug-loaded polydopamine, dispersed for 9 min, taken out, solidified by irradiation with blue light for 60 s, then frozen in a -20°C refrigerator, and freeze-dried in a freeze dryer to obtain a drug-loaded polydopamine hydrogel filled with a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold.
[0100] Example 3
[0101] A method for preparing a polycaprolactone stent filled with a drug-loaded polydopamine hydrogel comprises the following steps:
[0102] (1) At 37°C, 100 mg of mesoporous bioglass (average particle size between 300-900 nm, specific surface area between 200-1000 m 2 / g, with an average pore size of 2-40nm) was dispersed in 10mL of an aqueous solution containing 50mg of alendronate sodium, stirred at 800rpm for 4h, and freeze-dried to obtain drug-loaded mesoporous ceramics; 192mg of the drug-loaded mesoporous ceramics was added to 24mL of a 19mg / mL 2-methylimidazole aqueous solution, and 4mL of a 6mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the particles were washed and freeze-dried to obtain drug-loaded mesoporous ceramics@ZIF8 particles;
[0103] (2) Dissolve 10 g of polycaprolactone (molecular weight: 60,000 Daltons) in 100 mL of dichloromethane, add 20 g of gluconolactone and 2 g of the drug-loaded mesoporous ceramic @ZIF8 particles obtained in step (1), and mechanically stir at a speed of 400 rpm for 48 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone solution; pour the solution on a glass culture dish and place it in a ventilated state for 60 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone film; place the film in a printing barrel with a needle diameter of 0.35 mm , barrel temperature 80°C, needle temperature 85°C, fiber spacing 0.8mm×0.8mm, printing rate 10mm / s, fiber orientation "0-90°", air pressure 340kPa, scaffold layer height 85% of the needle diameter, printing layer by layer to obtain gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold; 50mg of gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was immersed in 100mL aqueous solution, and ultrasonicated at room temperature for 0.4 hours to obtain a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold;
[0104] (3) Dissolve 10 mg of metronidazole in 10 mL of a 3 mg / mL dopamine aqueous solution (pH = 9), stir at 400 rpm for 9 min, and freeze-dry to obtain drug-loaded polydopamine; dissolve 200 mg of methacryloyl carboxymethyl chitosan in 10 mL of a PBS solution containing 0.4% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then add 360 mg of drug-loaded polydopamine to obtain a hydrogel solution containing drug-loaded polydopamine; place 120 mg of the multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold obtained in step (2) into the hydrogel solution containing drug-loaded polydopamine, disperse for 3 min, take out, irradiate with blue light for 30 s to solidify, then freeze in a -20°C refrigerator, and freeze-dry in a freeze dryer to obtain a drug-loaded polydopamine hydrogel filled with a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold.
[0105] Example 4
[0106] A method for preparing a polycaprolactone stent filled with a drug-loaded polydopamine hydrogel comprises the following steps:
[0107] (1) At 25°C, 100 mg of mesoporous silica (average particle size between 50-500 nm, specific surface area between 500-1800 m 2 / g, with an average pore size of 2-20nm) was dispersed in 10mL of an aqueous solution containing 25mg of curcumin, stirred at 600rpm for 8h, and freeze-dried to obtain drug-loaded mesoporous ceramics; 432mg of drug-loaded mesoporous ceramics was added to 24mL of a 53mg / mL 2-methylimidazole aqueous solution, and 2mL of a 30mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the mixture was washed and freeze-dried to obtain drug-loaded mesoporous ceramics@ZIF8 particles;
[0108] (2) Dissolve 10 g of polycaprolactone (molecular weight 30,000 Daltons) in 12.5 mL of dichloromethane, add 5 g of gluconolactone and 0.5 g of the drug-loaded mesoporous ceramic @ZIF8 particles obtained in step (1), and mechanically stir at a speed of 300 rpm for 24 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone solution; pour the solution on a glass culture dish and place it in a ventilated state for 64 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone film; place the film in a printing barrel with a needle diameter of 0.2 mm, barrel temperature 60℃, needle temperature 65℃, fiber spacing 0.8mm×0.8mm, printing rate 15mm / s, fiber orientation "0-90°", air pressure 420kPa, scaffold layer height 75% of the needle diameter, printing layer by layer, to obtain gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold; 50mg of gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was immersed in 15mL aqueous solution, ultrasonicated at room temperature for 1 hour, to obtain a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold;
[0109] (3) 18 mg of penicillin was dissolved in 10 mL of 1.6 mg / mL dopamine aqueous solution (pH = 9.2), stirred at 600 rpm for 6 min, and freeze-dried to obtain drug-loaded polydopamine; 300 mg of methacryloyl carboxymethyl gelatin was dissolved in 10 mL of PBS solution containing 0.25% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then 120 mg of drug-loaded polydopamine was added to obtain a hydrogel solution containing drug-loaded polydopamine; 40 mg of the multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold obtained in step (2) was placed in the hydrogel solution containing drug-loaded polydopamine, dispersed for 12 min, then taken out, irradiated with blue light for 120 s to solidify, then placed in a -20°C refrigerator for freezing, and freeze-dried in a freeze dryer to obtain a drug-loaded polydopamine hydrogel filled with a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold.
[0110] Comparative Example 1
[0111] The only difference between Comparative Example 1 and Example 1 is that no gluconolactone is added in step (2) of Comparative Example 1, that is, the drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold obtained in step (2) of Comparative Example 1 does not have a pore structure, and the rest is the same as Example 1.
[0112] Specifically, step (2) of Comparative Example 1 is:
[0113] Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 50mL of dichloromethane, add 1.5g of drug-loaded mesoporous ceramic @ZIF8 particles, and stir magnetically at 500rpm for 72h to obtain a drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone solution. Pour the solution onto a glass petri dish and place it under ventilation for 72h to obtain a drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone film. Place the film in a printing barrel with a needle diameter of 0.25mm, a barrel temperature of 70°C, a needle temperature of 75°C, a fiber spacing of 0.8mm×0.8mm, a printing rate of 10mm / s, a fiber orientation of "0-90°", an air pressure of 360kPa, and a scaffold layer height of 80% of the needle diameter, and print the drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold layer by layer. 50 mg of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was immersed in 50 mL of aqueous solution and ultrasonicated at room temperature for 0.5 h to obtain drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold.
[0114] Comparative Example 2
[0115] The only difference between Comparative Example 2 and Example 1 is that polydopamine is not added in step (3) of Comparative Example 2, and the rest is the same as Example 1.
[0116] Specifically, step (3) of Comparative Example 2 is as follows:
[0117] 180 mg of methacryloylated sodium alginate was dissolved in 10 mL of PBS solution containing 0.3% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and 20 mg of gentamicin was added to obtain a drug-loaded hydrogel solution; 100 mg of a multi-level porous structured drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was placed in the drug-loaded hydrogel, dispersed for 6 minutes, taken out, solidified by irradiation with blue light for 90 seconds, then frozen in a -20°C refrigerator, and freeze-dried in a freeze dryer to obtain a drug-loaded hydrogel filled with a multi-level porous structured drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold.
[0118] Comparative Example 3
[0119] The difference between Comparative Example 3 and Example 1 is that in step (3) of Comparative Example 3, no antibacterial drug is added, that is, polydopamine is not loaded with drug, and the rest is the same as Example 1.
[0120] Specifically, step (3) of Comparative Example 3 is as follows:
[0121] 180 mg of methacryloyl sodium alginate was dissolved in 10 mL of PBS solution containing 0.3% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then 240 mg of polydopamine was added to obtain a hydrogel solution containing polydopamine; 100 mg of a multi-level porous structured drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was placed in the hydrogel solution containing polydopamine, dispersed for 6 minutes, taken out, solidified by irradiation with blue light for 90 seconds, then frozen in a -20°C refrigerator, and freeze-dried in a freeze dryer to obtain a polydopamine hydrogel-filled multi-level porous structured drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold.
[0122] Comparative Example 4
[0123] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 does not contain drug-loaded polydopamine particles, that is, no drug is added in step (3), and no polydopamine is added. The rest is the same as Example 1.
[0124] Specifically, step (3) of Comparative Example 4 is as follows:
[0125] 180 mg of methacryloyl sodium alginate was dissolved in 10 mL of PBS solution containing 0.3% phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution; 100 mg of a multi-level porous structured drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was placed in the hydrogel solution, dispersed for 6 minutes, taken out, solidified by irradiation with blue light for 90 seconds, and then frozen in a -20°C refrigerator, and then freeze-dried in a freeze dryer to obtain a hydrogel-filled multi-level porous structured drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold.
[0126] Comparative Example 5
[0127] The difference between Comparative Example 5 and Example 1 is that the mesoporous ceramic @ZIF8 particles in Comparative Example 5 are not loaded with drugs, that is, in step (1), no drugs for promoting tissue regeneration and repair are added, and the rest are the same as in Example 1.
[0128] Specifically, step (1) of comparative example 5 is as follows:
[0129] 300 mg of mesoporous calcium silicate (average particle size between 300-1000 nm, specific surface area between 300-900 m 2 / g, with an average pore size of 2-30nm) was added to 24mL of a 35mg / mL 2-methylimidazole aqueous solution, and 3mL of a 14mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the particles were washed and freeze-dried to obtain mesoporous ceramic@ZIF8 particles.
[0130] Comparative Example 6
[0131] The difference between Comparative Example 6 and Example 1 is that the drug-loaded ZIF8 particles in Comparative Example 6 do not contain mesoporous ceramics, that is, no mesoporous ceramics are added in step (1), and the rest is the same as Example 1.
[0132] Specifically, step (1) of Comparative Example 6 is as follows:
[0133] 0.05 mg of bone morphogenetic protein-2 was added to 24 mL of a 35 mg / mL 2-methylimidazole aqueous solution, and 3 mL of a 14 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the solution was washed and freeze-dried to obtain drug-loaded ZIF8 particles.
[0134] Comparative Example 7
[0135] The difference between Comparative Example 7 and Example 1 is that Comparative Example 7 does not contain ZIF8, that is, ZIF8 is not added in step (1), and the rest is the same as Example 1.
[0136] Specifically, step (1) of Comparative Example 7 is as follows:
[0137] At 0°C, 100 mg of mesoporous calcium silicate (average particle size between 300-1000 nm, specific surface area between 300-900 m 2 / g, with an average pore size between 2-30nm) were dispersed in 10mL of an aqueous solution containing 0.05mg of bone morphogenetic protein-2, stirred at 300rpm for 18h, and freeze-dried to obtain drug-loaded mesoporous ceramics.
[0138] Comparative Example 8
[0139] The difference between Comparative Example 8 and Example 1 is that Comparative Example 8 does not contain drug-loaded mesoporous ceramic @ZIF8 particles, that is, step (1) is not performed, and the rest is the same as Example 1.
[0140] Comparative Example 9
[0141] The difference between Comparative Example 9 and Example 1 is that Comparative Example 9 does not contain drug-loaded mesoporous ceramic @ZIF8 particles, gluconolactone, and drug-loaded polydopamine, and the rest is the same as Example 1.
[0142] Specifically, the preparation method of the polycaprolactone stent in Comparative Example 9 comprises the following steps:
[0143] 10g of polycaprolactone (molecular weight of 40,000 Daltons) was placed in a printing barrel, with a needle diameter of 0.25mm, a barrel temperature of 70°C, a needle temperature of 75°C, a fiber spacing of 0.8mm×0.8mm, a printing rate of 10mm / s, a fiber orientation of "0-90°", an air pressure of 360kPa, and a scaffold layer height of 80% of the needle diameter, and the scaffold was printed layer by layer to obtain a scaffold. 50mg of a polycaprolactone scaffold was soaked in 50mL of an aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain a polycaprolactone scaffold;
[0144] 180 mg of methacryloyl sodium alginate was dissolved in 10 mL of PBS solution containing 0.3% phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution; 100 mg of a polycaprolactone scaffold was placed in the hydrogel solution, dispersed for 6 minutes, taken out, solidified by irradiation with blue light for 90 seconds, then frozen in a -20°C refrigerator, and then freeze-dried in a freeze dryer to obtain a hydrogel-filled polycaprolactone scaffold.
[0145] Comparative Example 10
[0146] The difference between Comparative Example 10 and Example 1 is that in Comparative Example 10, a drug-loaded polydopamine coating is formed on the surface of the polycaprolactone stent and then filled with hydrogel, that is, steps (1) and (2) are the same as those in Example 1.
[0147] Steps (2) and (3) are as follows:
[0148] (2) Dissolve 10 g of polycaprolactone (molecular weight 40,000 Daltons) in 50 mL of dichloromethane, add 10 g of gluconolactone and 1.5 g of the drug-loaded mesoporous ceramic @ZIF8 particles obtained in step (1), and stir magnetically at a speed of 500 rpm for 72 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone solution; pour the solution on a glass culture dish and place it in a ventilated state for 72 h to obtain a gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone film; place the film in a printing barrel with a needle diameter of 0.25 m m, barrel temperature 70℃, needle temperature 75℃, fiber spacing 0.8mm×0.8mm, printing rate 10mm / s, fiber orientation "0-90°", air pressure 360kPa, scaffold layer height 80% of the needle diameter, printing layer by layer to obtain gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold; 50mg of gluconolactone / drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold was immersed in 50mL aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a multi-level porous structure of drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold;
[0149] (3) Dissolve 20 mg of gentamicin in 10 mL A 2 mg / mL dopamine aqueous solution (pH = 8.4) was added to the multi-level porous structure of the drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold, stirred at 300 rpm for 12 min, and freeze-dried to obtain a multi-level porous structure of the drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold containing a drug-loaded polydopamine coating; 180 mg of methacrylated sodium alginate was dissolved in 10 mL of a PBS solution containing 0.3% phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and then 100 mg of the multi-level porous structure of the drug-loaded mesoporous ceramic @ZIF8 / polycaprolactone scaffold containing a drug-loaded polydopamine coating was placed in the hydrogel solution, dispersed for 6 min, taken out, solidified by blue light irradiation for 90 s, then frozen in a -20°C refrigerator, and freeze-dried in a freeze dryer to obtain a hydrogel filled with a multi-level porous structure of the drug-loaded mesoporous ceramic @ZIF8 polycaprolactone scaffold containing a drug-loaded polydopamine coating.
[0150] Performance Testing
[0151] 1. In vitro cytotoxicity evaluation
[0152] L929 mouse fibroblasts that had been cultured for 24 hours and were growing vigorously were digested and prepared into a density of 1.0×10 5 / mL, inoculated in a 96-well plate, 100μL per well; after the cells grow into a monolayer, remove the original culture medium, add 100μL of the test sample (polycaprolactone scaffolds of Examples 1-4 and Comparative Examples 1-10) extract, blank control solution, positive control solution and negative control solution, each group of 6 duplicate wells, wherein the blank control solution is a complete culture medium containing 3g / L phenol; the positive control solution is an extract containing 0.3g / mL of high-density polyethylene in a complete culture medium at 37±1℃ for 24h; after the addition of samples, place the 96-well plate in a 37℃, 5% CO2 incubator for 24 hours; after culturing for 24h, aspirate the original culture medium, add 50μL per well MTT (1 mg / mL) was added and cultured for 2 hours. After the culture was completed, the supernatant was aspirated and 100 μL of 99.5% pure isopropanol was added to dissolve the crystals. The absorbance value was measured on an ELISA instrument with 570 nm as the main absorption wavelength and 650 nm as the reference wavelength to calculate the cell survival rate.
[0153] The cell viability was calculated according to the following formula: Cell viability (%) = 100 × OD 570e / OD 570b ;
[0154] OD 570e It is the average optical density of the test sample or control sample extract;
[0155] OD 570b is the average optical density of the blank.
[0156] The in vitro cell survival rates of the polycaprolactone scaffolds of the control group, Examples 1-4, and Comparative Examples 1-10 are shown in Table 1.
[0157] Table 1: In vitro cell survival rates of polycaprolactone scaffolds in the control group, examples 1-4, and comparative examples 1-10
[0158]
[0159] It can be seen from Table 1 that the polycaprolactone scaffold prepared in the present invention has no cytotoxicity.
[0160] 2. Hemolytic performance test
[0161] According to the amount of blood used in the test, blood is collected from the heart of a healthy rabbit, such as 10 mL of blood, and 0.5 mL of potassium oxalate solution with a mass concentration of 20 g / L is added to prepare fresh anticoagulated rabbit blood; 8 mL of fresh anticoagulated rabbit blood is taken and diluted with 10 mL of sodium chloride injection with a mass concentration of 9 g / L. The test sample group (Example 1-4, Comparative Example 1-10) is added according to the extraction ratio (0.2 g / mL), and then 10 mL of sodium chloride injection is added; 10 mL of sodium chloride injection is added to each tube of the negative control group; 10 mL of distilled water is added to each tube of the positive control group. Three tubes are operated in parallel in each group. After all the test tubes are placed in a constant temperature water bath at (37 ± 1) ° C for 30 minutes, 0.2 mL of diluted rabbit blood is added to each test tube, gently mixed, and placed in a 37 ± 1 ° C water bath for 60 minutes. Pour out the liquid in the tube and centrifuge at 800g for 5 minutes, aspirate the supernatant and transfer it to a cuvette, and measure the absorbance at a wavelength of 545nm using a spectrophotometer. The absorbance of the test group and the control group is the average of the three tubes. The absorbance of the negative control tube should not be greater than 0.03; the absorbance of the positive control tube should be 0.8±0.3, otherwise the test should be repeated.
[0162] The hemolysis rate was calculated as follows:
[0163] Hemolysis rate (%) = (absorbance of the test sample group - absorbance of the negative control group) / (absorbance of the positive control group - absorbance of the negative control group) × 100%.
[0164] The hemolysis rate results of the polycaprolactone stents of Examples 1-4 and Comparative Examples 1-10 are shown in Table 2.
[0165] Table 2: Hemolysis rate of polycaprolactone stents in Examples 1-4 and Comparative Examples 1-10
[0166]
[0167]
[0168] It can be seen from Table 2 that the hemolysis rate of the polycaprolactone stent prepared by the method of the present invention is less than 5%, and there is no hemolysis risk.
[0169] 3. In vitro drug release performance test
[0170] The in vitro drug release performance evaluation method is as follows: 500 mg of polycaprolactone scaffolds were immersed in 200 mL of PBS (pH = 7.4) in a constant temperature shaker at 37°C and 60 rpm, the test solution was collected regularly, and an equal amount of PBS was supplemented. The drug content of the collected test solution was determined by high performance liquid chromatography (HPLC), and compared with the total drug load in the product, the cumulative release rate of the drug was calculated.
[0171] The drug release curves of the polycaprolactone scaffolds for promoting tissue regeneration and repair in vitro are as follows: Figure 1 As shown; the drug release curves of the polycaprolactone stents in vitro for promoting tissue regeneration and repair in Example 1, Comparative Examples 1-4, 6-7, and 10 are as follows Figure 2 shown.
[0172] The in vitro antibacterial drug release curves of the polycaprolactone stents of Examples 1-4, Comparative Examples 1-2, 5-8, and 10 are as follows: Figure 3 As shown; the in vitro antibacterial drug release curves of the polycaprolactone stents of Example 1, Comparative Examples 1-2, 5-8, and 10 are as shown Figure 4 shown.
[0173] Depend on Figure 1-2 It can be seen that the release period of the polycaprolactone stents of Examples 1-4 for various drugs that promote tissue regeneration and repair is more than 5 weeks. Comparative Example 1 does not use gluconolactone, and its stent fibers do not contain a porous structure. The release rate of drugs that promote tissue regeneration and repair is significantly lower than that of Example 1, and the release period is significantly longer; Comparative Example 3 does not contain antibacterial drugs and has almost no effect on the drug release curve; Comparative Examples 2 and 4 do not contain polydopamine, and the drug-loaded ZIF8 particles in Comparative Example 6 do not contain bioactive ceramics, which has little effect on the release of drugs, and the release curves are close to those of Example 1. In Comparative Example 7, the drug-loaded mesoporous ceramic particles are not encapsulated with ZIF8, and the burst release is significantly increased compared with Example 1, and the release rate is significantly accelerated, with a cumulative release rate of nearly 90% at 5 weeks. Comparative Example 10 is changed to a PDA coating, which has a certain delaying effect on the release of drugs, and the drug release rate is between Example 1 and Comparative Example 1.
[0174] Depend on Figure 3-4 It can be seen that the release cycle of various antibacterial drugs in the polycaprolactone stents of Examples 1-4 exceeds 3 weeks. Compared with Example 1, Comparative Example 1 does not use gluconolactone, and its stent fiber does not contain a porous structure, and its antibacterial drug release rate is slightly lower than that of Example 1; Comparative Examples 5-8 have little effect on the release of antibacterial drugs embedded on the stent surface, and the release curves are also close to Example 1; In Comparative Example 2, the antibacterial drugs are not wrapped by polydopamine, and the antibacterial drugs are directly dispersed in the hydrogel. Compared with Example 1, the burst release is significantly increased, and the release rate is significantly increased. Comparative Example 10 forms a drug-loaded polydopamine coating on the surface of the polycaprolactone stent, and then fills the hydrogel, so that the release rate of Comparative Example 10 is significantly faster than that of Example 1.
[0175] 4. In vitro osteogenic differentiation test of pre-osteoblasts
[0176] The polycaprolactone scaffolds prepared in Examples 1-4 and Comparative Examples 1-10 were irradiated and sterilized, immersed in DMEM basal culture medium at a concentration of 10 mg / mL, and extracted at 120 rpm in a 37°C shaker for 24 h. After the extraction, the mixture of the polycaprolactone scaffold and the culture medium was centrifuged at 1000 rpm, and the supernatant was collected, which was the extract. The collected extracts were diluted 2 times with the corresponding DMEM culture medium, and finally 10% fetal bovine serum was added to obtain a conditioned medium.
[0177] Mouse embryonic osteoblast precursor cells (MC3T3-E1 cells) were cultured at 1×10 5 The cells were inoculated in a 24-well plate at a density of 100 cells / mL. After 24 hours of adherent culture, the conditioned medium was replaced and cultured in an incubator at 37°C and 5% carbon dioxide atmosphere. The culture medium was replaced every 2-3 days. After 7 days of culture, the osteogenic differentiation performance of MC3T3-E1 cells was detected by the alkaline phosphatase secreted by them and measured by the pNPP method. The specific steps are as follows: MC3T3-E1 cells were washed with PBS solution and immersed in a PBS solution containing 0.1 mol / L glycine, 1 mmol / L magnesium chloride and 0.05% Triton X-100 (octoxynol); after the cells were dissolved, the dissolved solution was evenly mixed with disodium p-nitrophenyl phosphate, and the mixed solution was placed at 37°C for 30 minutes; then, the mixed solution was added dropwise to a 96-well plate, and the absorbance value of each well at a wavelength of 405 nm was measured by an ELISA reader.
[0178] Definition of alkaline phosphatase activity unit: In diethanolamine (DEA) buffer at pH 9.8, at 37°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit (mmol / min / mg), also known as one DEA enzyme activity unit. In glycine buffer at pH 9.6, at 25°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one glycine enzyme activity unit. One glycine enzyme activity unit is approximately equivalent to 3 DEA enzyme activity units. Based on the definition of enzyme activity, the alkaline phosphatase activity in the sample is calculated. The alkaline phosphatase activity of the polycaprolactone scaffolds of Examples 1-4 and Comparative Examples 1-10 is shown in the figure. Figure 5 shown.
[0179] Depend on Figure 5It can be seen that the polycaprolactone scaffolds of Examples 1-4 of the present invention have a good effect of inducing cell secretion of alkaline phosphatase. Comparative Example 1 does not use gluconolactone, and the polycaprolactone scaffold does not have a multi-level pore structure. Its cell activity is lower than that of the scaffold with a multi-level pore structure, so it also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is slightly reduced compared with Example 1. Comparative Example 3 is not loaded with antibacterial drugs, and the alkaline phosphatase activity is close to that of Example 1. Comparative Examples 2 and 4 do not contain polydopamine with good biological activity, and the alkaline phosphatase activity is significantly reduced compared with Example 1. The drug-loaded ZIF8 particles in Comparative Example 6 do not contain bioactive ceramics, so it affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is also significantly reduced compared with Example 1. Comparative Example 7 does not contain ZIF8 with osteogenic activity, and the release of the drug is significantly accelerated, so it affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is significantly reduced compared with Example 1. The bioactive ceramic / ZIF8 particles in Comparative Example 5 are not loaded with drugs, and the alkaline phosphatase activity is significantly reduced compared with Example 1. Comparative Example 8 does not contain drug-loaded bioactive ceramic / ZIF8 particles, and the alkaline phosphatase activity is also significantly reduced compared with Example 1, and its alkaline phosphatase activity is lower than that of Comparative Example 5. Comparative Example 9 does not contain polydopamine with good biological activity, nor does it have a multi-level pore structure, drug-loaded mesoporous ceramic @ZIF8 particles and antibacterial drugs, and its alkaline phosphatase activity is the lowest. Comparative Example 10 is changed to form a polydopamine coating, and its alkaline phosphatase activity is between Comparative Example 2 and Example 1.
[0180] 5. Antibacterial performance test
[0181] Take fresh slant cultures of Staphylococcus aureus and Escherichia coli, count the live bacteria in the bacterial suspension, and prepare a 5×10-60 suspension with 0.03 mol / L PBS (pH=7.2-7.4) containing 1% peptone. 5 -10×10 6 cfu / mL of bacterial suspension. Place the polycaprolactone stent samples of Examples 1-4 and Comparative Examples 1-10 in sterile dishes respectively, add 50 μL of bacterial suspension on each sample, record the time of adding bacteria to each tube, inoculate the blood plate 60 minutes after adding bacteria, and place the sample in a 5mL nutrient broth tube. Incubate the blood plate and broth tube inoculated with bacteria at 37°C for 48 hours, observe the preliminary results, and continue to culture in the sterile growth tube until the 28th day. If the broth tube is turbid and the blood plate has bacterial growth, it is recorded as positive, indicated by (+); if it is still clear on the 35th day, it is considered as sterile growth, indicated by (–).
[0182] The test results of the antibacterial properties of the polycaprolactone stents of Examples 1-4 and Comparative Examples 1-10 are shown in Table 3.
[0183] Table 3: Test results of antibacterial properties of polycaprolactone stents in Examples 1-4 and Comparative Examples 1-10
[0184]
[0185] It can be seen from Table 3 that the polycaprolactone stents prepared in Examples 1-4 of the present invention all have good long-term antibacterial effects and can grow aseptically for 35 days. Comparative Example 9 does not contain ZIF8 or antibacterial drugs and has no antibacterial effect.
[0186] In summary, the polycaprolactone stent body of the present invention has macroscopic macropores (fiber gaps) and microscopic pores (fiber surface holes) at the same time, significantly improving the specific surface area of the polycaprolactone stent body, accelerating the degradation of polycaprolactone and releasing more acidic degradation products, thereby accelerating the degradation of polydopamine and accelerating the release of the antibacterial drugs embedded inside it. At the same time, macroscopic macropores and microscopic pores can also significantly improve the surface roughness of the polycaprolactone stent body, achieving the purpose of promoting the adhesion of polycaprolactone stent cells. The drug-loaded mesoporous bioceramics are embedded in ZIF8, which can delay the release of drugs, achieve the effect of long-term sustained and controlled release, improve antibacterial properties, induce osteogenic differentiation of stem cells, and are suitable for repair and regeneration of bone tissue defects under infection, and bioactive ceramics can enhance the biological activity and mechanical strength of drug-loaded particles. In addition, the hydrogel and drug-loaded polydopamine particles filled in the stent pores can improve the mechanical strength and biological activity of the stent and give the stent antibacterial properties.
[0187] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polycaprolactone stent, characterized in that: It comprises a polycaprolactone stent body, and drug-loaded mesoporous ceramics and zeolite imidazolate skeleton materials embedded in the polycaprolactone stent body; The drug-loaded mesoporous ceramic is embedded in the zeolite imidazolate framework material; The matrix material of the polycaprolactone stent body is polycaprolactone, and the fibers of the polycaprolactone and the surfaces of the polycaprolactone fibers both have micron pore structures, and the size of the micron pore structures between the fibers of the polycaprolactone is larger than the size of the micron pore structures on the surfaces of the polycaprolactone fibers; The micron pore structure is filled with hydrogel; and drug-loaded polydopamine is embedded in the hydrogel.
2. The polycaprolactone stent according to claim 1, characterized in that: The polycaprolactone stent body is a 3D printed stent; and / or the molecular weight of the polycaprolactone is 27,000-110,000 Daltons.
3. The polycaprolactone stent according to claim 1, characterized in that: The size of the micropore structure between the fibers of the polycaprolactone is 200-650 μm; and / or the size of the micropore structure on the surface of the fiber of the polycaprolactone is 0.9-110 μm.
4. The polycaprolactone stent according to claim 1, characterized in that: The mesoporous ceramic in the drug-loaded mesoporous ceramic includes at least one of mesoporous silicon, mesoporous calcium silicate, mesoporous magnesium silicate, mesoporous zinc silicate, mesoporous strontium silicate, mesoporous bioglass, and mesoporous hydroxyapatite; and / or, the particle size of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 45-1100nm; and / or, the specific surface area of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 140-2000m 2 / g; and / or, the average pore size of the mesoporous ceramic in the drug-loaded mesoporous ceramic is 2-45nm.
5. The polycaprolactone stent according to claim 1, characterized in that: The drug in the drug-loaded mesoporous ceramic includes a drug that promotes tissue regeneration and repair; and / or, the hydrogel includes at least one of methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chondroitin sulfate, methacrylated chitosan, methacrylated carboxymethyl chitosan, methacrylated gelatin, methacrylated sodium alginate, hyaluronic acid, silk fibroin, chondroitin sulfate, chitosan, carboxymethyl chitosan, gelatin, and sodium alginate; and / or, the drug in the drug-loaded polydopamine includes an antibacterial drug.
6. The method for preparing the polycaprolactone stent according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing a mesoporous ceramic and an aqueous solution containing a drug, and drying them to obtain a drug-loaded mesoporous ceramic; mixing the drug-loaded mesoporous ceramic and an aqueous solution of 2-methylimidazole, and then adding an aqueous solution of a zinc source to react, to obtain a material in which a zeolite imidazole ester framework material is embedded in the drug-loaded mesoporous ceramic; (2) mixing polycaprolactone, a solvent, gluconolactone and the material obtained in step (1) for embedding the drug-loaded mesoporous ceramic with the zeolite imidazolate skeleton material to obtain a mixed solution, preparing the mixed solution into a film, and then printing to obtain gluconolactone / drug-loaded mesoporous ceramic@zeolite imidazolate skeleton material / polycaprolactone scaffold, and placing it in an aqueous solution, ultrasonically treating it, and obtaining drug-loaded mesoporous ceramic@zeolite imidazolate skeleton material / polycaprolactone scaffold; (3) adding the drug-loaded polydopamine to a hydrogel solution containing a photoinitiator to obtain a hydrogel solution containing the drug-loaded polydopamine; then placing the drug-loaded mesoporous ceramic @ zeolite imidazole ester framework material / polycaprolactone scaffold obtained in step (2) into the hydrogel solution containing the drug-loaded polydopamine, then taking it out and solidifying it to obtain the polycaprolactone scaffold.
7. The preparation method according to claim 6, characterized in that: In step (1), the mass ratio of the drug to the mesoporous ceramic is (0.0005-0.055):1; and / or, the concentrations of 2-methylimidazole and the drug-loaded mesoporous ceramic in the 2-methylimidazole aqueous solution are 17-58 mg / mL and 7-20 mg / mL, respectively; and / or, the zinc source aqueous solution includes a zinc nitrate aqueous solution; the concentration of zinc nitrate in the zinc nitrate aqueous solution is 5.5-33 mg / mL; and / or, the volume ratio of the 2-methylimidazole aqueous solution to the zinc source aqueous solution is (5.5-13):
1.
8. The preparation method according to claim 6, characterized in that: In step (2), the mass ratio of the material of the gluconolactone and zeolite imidazolate skeleton material encapsulating the drug-loaded mesoporous ceramic to polycaprolactone is (0.45-3.3):(0.05-0.33):1; and / or, the mass volume ratio of the polycaprolactone to the solvent is (0.45-9) g:10 mL; and / or, the mass volume ratio of the gluconolactone / drug-loaded mesoporous ceramic@zeolite imidazolate skeleton material / polycaprolactone scaffold to the aqueous solution is 1 mg:(0.27-4.5) mL.
9. The preparation method according to claim 6, characterized in that: In step (3), the preparation process of the drug-loaded polydopamine is to mix the drug and the dopamine aqueous solution, stir and obtain; the concentration of dopamine in the dopamine aqueous solution is 1.5-4.5 mg / mL; the mass volume ratio of the drug to the dopamine aqueous solution is (9-33) mg:10 mL; and / or, the concentration of hydrogel in the hydrogel solution is 1.4-3.3%; and / or, the mass volume ratio of the drug-loaded polydopamine to the hydrogel solution is (11-52) mg:1 mL; and / or, the mass volume ratio of the drug-loaded mesoporous ceramic @ zeolite imidazole ester framework material / polycaprolactone stent to the hydrogel solution containing the drug-loaded polydopamine is (0.04-0.18) g:10 mL; and / or, the implantation time is 2.5-13 min.
10. Use of the polycaprolactone scaffold according to any one of claims 1 to 5 in the preparation of bone tissue defect repair and regeneration products.
Citation Information
Patent Citations
Nanoporous magnesium silicate microsphere / PBS (poly(butylene succinate)) composite scaffold, composite scaffold coated with protein, preparation methods and application
CN107412856A
Preparation method and application of nanofiber material taking polycaprolactone as matrix
CN115737909A
Regenerative bone scaffold as well as preparation method and application thereof
CN118924949A
Structure of observation deck for adding ICT function
KR102654069B1